Penggunaan Media Pembelajaran Flipbook Terhadap Peningkatan Hasil Belajar Siswa Pelajaran Akidah - Nurul Aulia Lailatul Udl-Hiyah; Indah Nurhidayati; Praptiningsih (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2023)
This research aims to improve learning outcomes in the subject of moral beliefs using Flipbook learning media for grade 3 students at MIN 3 Sukoharjo. Type of classroom action research (PTK) or Classroom action research design. This research is more about solving a problem whose results are described thoroughly. The research subjects in this PTK were class III students at MIN 3 Sukoharjo. This research consists of 2 cycles, namely cycles I and II, each cycle consisting of 4 stages, namely planning, implementation, observation, reflection. The research results showed that in the pre-cycle actions, the average value of learning outcomes was only 63.92. In the first cycle of action the average learning outcome was 69.76. In the second cycle of action, the average value of learning outcomes was 80.12. The number of students who met the KKM score (>70) in the pre-cycle was 12 students or 48%. Students who met the KKM score (≥70) in cycle I were 16 students or 64%, while in cycle II there were 22 students or 88%. The increase in learning outcomes from the results of pre-cycle actions to cycle II of initial reading has reached the KKM value (≥70) and achieved the performance indicators (≥75) targeted by researchers.